Necessary and sufficient condition of isomorphism for multiplicative and additive systems without continuity condition with the accuracy up to grinding divisions - Kozachenko, M. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 1988)
Получено необходимое недостаточное условие изоморфизма мультипликативных и аддитивных систем без условия непрерывности с точностью до измельчающихся разбиений.